Empowering the Creative Economy as a Survival Strategy for Single Mothers After Unregistered Divorce in Aceh - Rafiqah Rafiqah; Muhammad Isa; Ali Azis Usman Harahap; Abdulloh Mama (Fakultas Syariah IAIN Langsa, 2025)
Unregistered (siri) divorce in Aceh produces significant socio-legal and economic vulnerabilities for single mothers due to the absence of formal legal recognition and limited access to state resources. While the creative economy is often promoted as an inclusive empowerment strategy, single mothers affected by unregistered divorce continue to face severe constraints in accessing capital, institutional support, and targeted policies. Using a qualitative approach guided by the Sustainable Livelihoods Framework (SLF), this study examines how single mothers mobilize livelihood assets to sustain economic resilience amid legal invisibility. Based on interviews with single mothers, creative economy actors, and government officials in Aceh, the findings demonstrate that creative economic engagement enhances economic independence and social capital, despite persistent barriers to financial and institutional support. This study underscores the need for targeted legal and policy interventions to ensure business sustainability and strengthen the socio-legal position of single mothers in Aceh.